Interaction of Religion and Medicine in the Period of Existential Challenges: Ukrainian Context - Utiuzh, Irina (Occasional papers on religion in Eastern Europe, 2021)
The social transitivity of Ukrainian society has only intensified as a result of the implementation of quarantine restrictions in March 2020 that covered various areas of the country's social life. In the situation of transferring most industries and services to remote work, the problems of an existential choice in citizens' perception of quarantine restrictions and the need to ensure their own economic and physiological survival in a severe socio-economic crisis in Ukraine and military aggression by Russia appeared in 2014. In this context, it remains relevant to define how medical and religious organizations should help Ukrainian citizens adapt to the existential and social challenges provoked by the COVID-19 pandemic. The peculiarities of Ukrainians' perception of the premature death threat, the growing sense of helplessness, and the impact of fatalities provoked by COVID-19 are exacerbated in the modern Ukrainian society by the post-traumatic syndrome of the Holodomor of 1932-1933, the Chernobyl disaster, annexation of the Crimea and military aggression by Russia. The conclusions of the article outline the similarities with global trends in Ukrainians' perception of COVID-19 (confusion, panic and suicidal moods) and features of the national perception of the existential threat: critical attitude of Ukrainians to public medicine, focus on self-medication, mostly positive attitude of an individual to doctors, confidence of the citizens of Ukraine that only the rich will receive proper care and vaccination, etc. The article also analyzes the role of religious organizations in the process of adaptation of Ukrainian society to the existential challenges of today in the field of palliative care and psychological support of victims of hostilities, including the adaptation of citizens to live in quarantine and a post-pandemic environment.